2015
DOI: 10.1097/sla.0000000000000973
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Anastomotic Leak After Colon Resection for Cancer

Abstract: Anastomotic leak after colon resection for cancer is a frequent, relevant complication. Patients, surgical technique, and hospital are all important determining factors of anastomotic leak risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
123
0
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 302 publications
(138 citation statements)
references
References 41 publications
6
123
0
9
Order By: Relevance
“…Other studies obtained similar results (OR = 1.49–3.2) [5, 18, 23, 24]. The higher risk of AL in male patients may be due to their narrow pelvis, which leads to a more complicated operation compared to female patients with a broader pelvis.…”
Section: Discussionsupporting
confidence: 53%
“…Other studies obtained similar results (OR = 1.49–3.2) [5, 18, 23, 24]. The higher risk of AL in male patients may be due to their narrow pelvis, which leads to a more complicated operation compared to female patients with a broader pelvis.…”
Section: Discussionsupporting
confidence: 53%
“…HS may also reduce the inflammatory response and thereby reduce anastomotic leakage. [12,29] In the experimental setting, HS prevents adverse structural and functional alterations of the anastomotic position by improving the intestinal blood flow and modulating the systemic and local immune response. [30] This hypothesis on background mechanisms was not investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term oncological and quality of life impact are well-established. [8][9][10][11] However, Frago et al have shown good results following emergency surgical resection, but only in selected cases performed by specialist colorectal surgeons. 13 In 1991, Dohmoto introduced the use of a self-expanding metallic stent (SEMS) as a palliative treatment for malignant Conclusions: The use of self-expanding metallic stents as a bridge to surgery is a safe option in the urgent treatment of obstructive left colon cancer, with similar short and long-term results compared to direct surgery, inferior mean costs and a higher rate of primary anastomosis.…”
Section: Introductionmentioning
confidence: 94%
“…[1][2][3] Despite medical and surgical advances, this emergency surgery continues to have a high morbidity (30-60%) and mortality (10-30%) compared to elective surgery (mortality rate less than 5%). [4][5][6][7][8] This difference could be for two reasons: first of all, in emergency surgery the patient is not adequately prepared and optimized in terms of hydration, nutritional status, electrolyte balance, etc. Moreover, emergency surgery is often performed by general surgeons rather than colorectal specialists, with a resulting ''surgeon-dependent'' negative effect.…”
Section: Introductionmentioning
confidence: 99%